RECENT ADVANCES IN CEMENT CHEMISTRY AND APPLICATIONS: A REVIEW - Alisi, Ikechkwu O.; Musa, Abubakar; Jacob, Adikwu G. (FUDMA JOURNAL OF SCIENCES, 2025)
This study provides a survey of the chemistry and applications of the various kinds of cement produced by various industries in recent times.  Cement-based products are widely used in the construction of buildings, roads, bridges and oil well drilling. The primary components of cement are limestone, clay and shale. Cement forms a composite known as mortar when mixed with water and sand. When mixed with water, sand and gravel it forms concrete. There are various types of cement produced and marketed worldwide. Ordinary Portland cement is the most widely used type of cement in various construction works. This cement is a fine grey/white powder consisting of a mixture of calcium silicates, aluminates, and aluminoferrites. It is a mixture of different inorganic oxides such as CaO, SiO2, Al2O3 and Fe2O3, The ability to understand the different properties of the various types of cement helps one to make informed decision when selecting materials for a particular application.
Keywords: Cement chemistry; Limestone; Concrete; Portland cement; Cement production; Clinker formation